RELIGIOUS COPING, STRESS AND BURNOUT AT RELIGIOUS EDUCATION TEACHERS - Hreciński, Piotr (Studia Psychologica: Theoria et praxis, 2017)
The teaching profession is exposed to stress and burnout. According to the job demands–resources model, employees with few resources and high demands are exposed to burnout especially. A subject of the study was the relationship among three variables: religious coping (Brief RCOPE) given as particular personal resources, stress (SSN) considered as job demands, and burnout (MBI). This study examined 419 RE teachers. It was found that the negative religious coping positively correlated with every dimension of burnout, whereas positive religious coping negatively correlated with burnout. Moreover, positive religious coping moderated the relation between stress and burnout. More specifically, the relation was weaker for teachers with high positive religious coping.